The influence of modified vegetable oils on tool failure mode and wear mechanisms when turning AISI 1045 - Abdul Sani, Amiril Sahab; Abd Rahim, Erween; Sharif, Safian; Sasahara, Hiroyuki (Elsevier, 2019)
A newly developed bio-based metalworking fluid (MWF) from Jatropha oil is evaluated in this study as part of the research purposes for ‘greener’ machining activity. This work focuses on the machinability effects of using ionic liquids (ILs) added Jatropha-based MWFs of different weight concentrations (1, 5 and 10%). The machining performance on AISI 1045 steel was analyzed based on the lubrication effects of the novel modified Jatropha-based lubricants (MJO). Experimental results for the ILs added MJOs, depending on the ILs treat rate, were superior to the synthetic ester-based MWF. In addition, MJO + AIL10% outperformed all the other lubricant samples on cutting force and temperature, surface roughness, wear mechanisms and tool life of the uncoated cermet inserts during the machining process.